Optimal Design for LCL-SRC Type - Dakheel, Adel M. (Basrah Journal for Engineering Sciences, 2006)
The LCL Series Resonant Converter (LCL-SRC) type offer nearly load- independent output voltage under some operating conditions. By this way the output voltage can be regulated against a wide load and line variations with a small variation of switching frequency. In this paper a simple method for optimization of LCL-SRC is presented. This method takes the stored energy as a theoretical index to obtain the minimal size of the converter inductors L1 and L2 which contribute significantly to the converter size and weight. The Rac method for the analysis of resonant converter is discussed. This method was found fairly accurate for operation above resonant frequency.